The master guide to drawing anime. 5-minute characters : super-simple lessons from the best-selling series - Hart, Christopher, 1957- (Hart, Christopher, 1957- Drawing with Christopher Hart., 2020)
Presents step-by-step illustrated instructions for learning to draw and color anime characters. Includes lessons on drawing facial expressions on heads at different angles, along with different poses and actions.